2001
DOI: 10.1667/0033-7587(2001)156[0526:ldhich]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Hypersensitivity in Chinese Hamster V79 Cells Targeted with Counted Protons Using a Charged-Particle Microbeam

Abstract: The Gray Laboratory charged-particle microbeam has been used to assess the clonogenic ability of Chinese hamster V79 cells after irradiation of their nuclei with a precisely defined number of protons with energies of 1.0 and 3.2 MeV. The microbeam uses a 1-microm silica capillary collimator to deliver protons to subcellular targets with high accuracy. The detection system is based on a miniature photomultiplier tube positioned above the cell dish, which detects the photons generated by the passage of the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
0
65
0
Order By: Relevance
“…The tendency would be that cells show either HRS or BE, but both phenomena are mutually exclusive. However, it is worth noting that this study finds no bystander cell killing in a human glioblastoma which yet shows bystander micronuclei formation after a particles irradiation (Burdak-Rothkamm et al, 2006;Shao et al, 2005Shao et al, ,2003aShao et al, , 2004; also HRS has been detected in hamster cells (Schettino et al, 2001;Tsoulou et al, 2001), as well as the bystander effect for survival (Schettino et al, ,2003. Again, those experiments used different protocols, and looked at different endpoints, and therefore, conclusions are difficult.…”
Section: Be and Other Non-targeted Effectsmentioning
confidence: 70%
See 2 more Smart Citations
“…The tendency would be that cells show either HRS or BE, but both phenomena are mutually exclusive. However, it is worth noting that this study finds no bystander cell killing in a human glioblastoma which yet shows bystander micronuclei formation after a particles irradiation (Burdak-Rothkamm et al, 2006;Shao et al, 2005Shao et al, ,2003aShao et al, , 2004; also HRS has been detected in hamster cells (Schettino et al, 2001;Tsoulou et al, 2001), as well as the bystander effect for survival (Schettino et al, ,2003. Again, those experiments used different protocols, and looked at different endpoints, and therefore, conclusions are difficult.…”
Section: Be and Other Non-targeted Effectsmentioning
confidence: 70%
“…Nevertheless, Schettino et al (2001) led some clonogenic assays on a hamster cell line and showed that most colonies contained between 75 cells and 85 cells, and that the proportion of those colonies decreased with dose. Therefore, Equation 2.3 is appropriate to measure the change in proliferation of cells occurring after radiation.…”
Section: The Clonogenic Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, experimental data on proton RBE versus LET d (Folkard et al 1996, Belli et al 1989, 1993, Perris et al 1986, Coutrakon et al 1997, Wouters et al 1996, Schettino et al 2001 and proton RBE versus (α/β) x (Gerweck andKozin 1999, Paganetti et al 2000) indicate that RBE increases with increasing LET d (note that for protons the eventual decrease with LET d happens at LET d values irrelevant for clinical considerations) but decreases with increasing (α/β) x . The current data sets used to relate RBE with LET d and (α/β) x are subject to uncertainties (Carabe et al 2012, Carabe 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly using a microbeam Schettino et al (2001), found low dose hypersensitivity with 3.2 MeV protons below 1 Gray, a result which cannot be observed with survival curves obtained with equivalent broadbeams. However, it was clear that a comparison above 1 Gy gave very similar results for both 1 and 3.2 MeV protons.…”
Section: Discussionmentioning
confidence: 84%